(untitled) (INNOVATIVE ECONOMY, 2021)
Pushkar O.I., Tataryntseva Yu.L., Makarenko A.B., Pastushenko O.B. MODEL OF FINANCING AN INNOVATIVE PROJECT IN HIGH-TECH BUSINESS (ON THE EXAMPLE OF GAME INDUSTRY) Purpose. The aim of the article is to develop the methodical recommendations on formation of model of financing of the innovative project in high-tech business (on an example of the game industry). Methodology of research. The following methods of scientific research were used in the process of writing this article: comparison - to determine the differences and common features of the phenomena under study; grouping - to determine the project of financing methods, crowd funding models; synthesis and analysis - to detail the object of study, by breaking it down into parts. Findings. The article provides guidelines for the development and implementation of a model for financing an innovative project in high-tech business, which contains three components. Peculiarities of business promotion in the field of game industry, which influence the choice of sources of financing, are determined. It is substantiated that the financing of innovative business should combine different sources according to the phases of project implementation. It was found that the use of non-traditional sources, in particular crowd funding, is in great demand. The main models of crowd funding used in modern conditions of financing of innovative enterprises are generalized. Relevant models of working capital management at different phases of innovation project implementation are determined. Originality. The scientific novelty of the research results is the improvement of theoretical and methodological provisions for the formation of a model for financing an innovative project in high-tech business on the example of the game industry. The key parameters of this model are the presence of three components that allow to take into account the specifics of the game industry: the choice of production model, the choice of funding sources, the choice of funding model. Practical value. The functioning of the model of financing an innovative project in high-tech business reflects the experience of corporate finance management, financial modelling and adaptation of these practices for enterprises in the field of innovation. The results of the study will be useful for application in the practice of domestic enterprises that implement innovations, will attract investors. Key words: financing model, game industry, innovative project, high-tech business, crowd funding.